Identification of 9-Gene Epithelial–Mesenchymal Transition Related Signature of Osteosarcoma by Integrating Multi Cohorts. (11th December 2020) - Yiqi, Zhang; Ziyun, Liu; Qin, Fu; Xingli, Wang; Liyu, Yang
Background: The prognosis of patients with osteosarcoma is still poor due to the lack of effective prognostic markers. The EMT (epithelial–mesenchymal transition) serves as a promoter in the progression of osteosarcoma. This study systematically analyzed EMT-related genes to explore new markers for predicting the prognosis of osteosarcoma. Methods: RNA-Seq data and clinical information were obtained from the GEO database; GSVA and GSEA analysis were used to enrich pathways related to osteosarcoma progression; LASSO method analysis was used to construct the prognosis risk signature. The "Nomogram" package generated the risk prediction nomogram, and its clinical applicability was evaluated by decision curve analysis (DCA). Results: GSVA and GSEA analysis showed that the EMT signaling pathway was closely related to osteosarcoma progression. A 9-genes signature (LAMA3, LGALS1, SGCG, VEGFA, WNT5A, MATN3, ANPEP, FUCA1, and FLNA) was constructed. The overall survival (OS) of the high-risk scores group was significantly lower than the low-risk scores group. The 9-gene signature demonstrated good predictive accuracy. Cox regression analysis showed that the 9-gene signature provided independent prognostic factors for osteosarcoma patients. In addition, the predictive nomogram model could effectively predict the prognosis of osteosarcoma patients. Conclusion: This study constructed a 9-gene signature as a new prognostic marker to predict osteosarcoma patients' survival.